Induction of oestrus in delayed pubertal cross-bred heifers - SIRMOUR, SANJEEV; NEMA, S P; SINGH, B K; SUKLA, S P (The Indian Journal of Animal Reproduction, 2023)
Buserelin acetate (Gn RH analogue) alone or in combination wilh oestradiol valerate or sodium salt of 4 dimethyl amino2 methyl phenyl phosphoric acid was administered parentrally in delayed pubertal crossbred heifers for induction of oestrus. Sixtreatment combination groups and two control groups comprised of total 48 heifers having six randomly allocated animals in eachgroup. Efficacy of these drugs was judged on the basis of per cent heifers having induced oestrus, oestrus induction interval,oestrus intensity score and conception rate.In five of the six treatment groups oestrus induction efficacy was 83.33% where as heifers receiving Buserelin acetate (80μg) alone IVSM had 50 % oestrus induction. The oestrus induction interval ranged from 6-28 days having the least interval ( 10.00± 0.45 days) in oestradiol valerate primed and have received 200 μg buserelin acetate im had a comparable oestrus intensity (81.60± 0.98) to cyclic control (84.50 ± 1.57) group. Though the oestrus induction interval was slightly higher ( 16.60.± 2. 70 days) inphosphorus supplementation and 200 μg buserelin acetate im group. These animals had I 00% conception rate.
Keywords: Cross-breed heifers; delayed puberty; oestrus induction; GnRH